Kepuasan Kerja Dalam Organisasi: Tinjauan Literatur Sistematis - Laila Maulidiya (Jejaring Administrasi Publik, 2025)
Employees and job satisfaction have become a major focus of management studies around the world. It is a key concern for organizations in assessing individual performance. Employee performance in the workplace is measured by how they carry out their responsibilities in ways that contribute to the achievement of organizational goals and create a sense of satisfaction in their work. This study uses the Systematic Literature Review (SLR) methodology. The studies were obtained and selected from reputable journal publications indexed in Scopus. A total of 24 articles were analyzed in this review. Significant findings are how employee attitudes and performance in the workplace are influenced by how satisfied they are with their jobs. The implications of these findings are particularly important for public organizations, where job satisfaction is often closely linked to the effectiveness of public service delivery, organizational stability, and the successful implementation of public policies. In conclusion, first, the most frequently cited factors determining job satisfaction are human resources management (HRM), employee relationships, and workplace environment. Second, the most recommended ways to improve job satisfaction are job performance, job security, and leadership. This synthesis suggests that strategies for improving job satisfaction are not generic but must be adapted to the specific characteristics of public sector organizations, which are often hierarchical, bureaucratic, and face resource limitations. Keywords: Job satisfaction, employee relations, systematic literature review